Pelaksanaan Sistem Inovasi di Indonesia - Latifa Suhada Nisa (Jurnal Kebijakan Pembangunan, 2022)
The Indonesian government has made various efforts to increase global competitiveness. One of which is through increased innovation. In doing so, it should be integrated within a system to ensure its implementation and sustainability, with actors, institutions, interaction relationships and productive processes that influence the direction of development, speed and diffusion of innovation. Its implementation in the regions is known as the regional innovation system, which is an integral part of the national innovation system. This paper aims to describe the implementation of the innovation system in terms of regulation, implementation, monitoring and evaluation. The method used is desk study, by analyzing secondary data descriptively according to related topics. Based on the literature review, it is known that the implementation of innovation in Indonesia runs within a national innovation system. The implementation of innovation in the central and local governments is based on the law and regulations underlying the innovation system in Indonesia. Programs and activities are carried out to support the implementation of innovation, such as the implementation and strengthening of the Regional Innovation System (SIDa), the construction of a Science Techno-Park, and the assessment of the regional innovation index. The preparation of the SIDa Roadmap was carried out as one of the strengthening steps to create a conducive innovation system. One form of monitoring and evaluation carried out by the central government on implementing innovation is through the measurement of the regional innovation index, where awards and guidance are given to regions based on their innovation predicate. Local governments need to prepare an innovation database as a strategic step in developing innovation, intellectual property and information, as well as encouraging the growth and development of a culture of innovation through education, training, appreciation, and innovation campaigns. Abstrak Pemerintah Indonesia melakukan berbagai upaya untuk mendorong peningkatan daya saing global. Salah satunya melalui inovasi. Untuk menjamin pelaksanaan dan keberlangsungan inovasi, maka inovasi dijalankan dalam suatu sistem, dimana di dalamnya terdapat pelaku, kelembagaan, hubungan interaksi dan proses produktif yang mempengaruhi arah perkembangan, kecepatan dan difusi dari suatu inovasi. Pelaksanaannya di daerah dikenal dengan istilah sistem inovasi daerah, merupakan bagian integral dari sistem inovasi nasional. Tulisan ini bertujuan untuk menggambarkan bagaimana pelaksanaan sistem inovasi, dari segi regulasi, implementasi, monitoring dan evaluasi. Metode yang digunakan adalah desk study, dengan menganalisis data sekunder secara deskriptif sesuai dengan topik bahasan terkait. Berdasarkan telaah pustaka yang dilakukan, diketahui bahwa pelaksanaan inovasi berjalan dalam suatu wadah sistem inovasi nasional. Secara regulasi, sudah terdapat peraturan yang menjadi payung hukum pelaksanaan inovasi di tingkat pusat dan daerah. Banyak program/kegiatan yang dilakukan untuk mendukung pelaksanaan inovasi, seperti pelaksanaan dan penguatan Sistem Inovasi Daerah (SIDa), pembangunan Science Tecno-Park, dan penilaian indeks inovasi daerah. Penyusunan Roadmap SIDa dilakukan sebagai salah satu langkah penguatan untuk menciptakan sistem inovasi yang kondusif. Salah satu bentuk monitoring dan evaluasi yang dilaksanakan pemerintah pusat terhadap pelaksanaan inovasi adalah melalui pengukuran indeks inovasi daerah, dimana penghargaan dan pembinaan diberikan kepada daerah berdasarkan predikat inovasinya. Pemerintah daerah perlu melakukan penyusunan basis data inovasi sebagai langkah strategis pengembangan inovasi, dan juga pengembangan kekayaan intelektual serta informasi, serta mendorong tumbuh kembang budaya inovasi melalui jalur pendidikan, pelatihan, apresiasi, dan kampanye inovasi.